Double cultural belonging: being children of luso brasilians couples in Portugal - Martins Mendes, Carla (2022)
The article discusses the results of a field research on generational transmission in the second generation of Brazilian immigrants in Portugal. It aims to understand the construction of the double cultural belonging of children of Portuguese-Brazilian couples in Portugal. A qualitative research was carried out in which twelve participants were interviewed. The results were analyzed according to the content analysis method, thematic-category aspect and discussed from the theoretical framework of psychoanalysis and the social sciences. We discussed the categories of double cultural belonging and ties to families of origin. We conclude that family dynamics favored biculturalism, anchored in the identification with aspects considered positive in both cultures. The bonds with families of Brazilian origin were more invested in the private sphere, as a form of protection against stigmatization.